A model united nations experiment on climate negotiations - Elisa Hofmann; Lucas Kyriacou; Klaus M. Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
Weitzman (2014) proposed that focusing international climate negotiations on a uniform carbon price is more effective than Paris style negotiations in achieving ambitious climate action. We put this hypothesis to an experimental test by simulating international negotiations on climate change in collaboration with Model United Nations associations. This novel experimental format combines some of the advantages of lab and field experiments. Our results show that negotiating a common commitment on a uniform carbon price yields significantly higher emissions reductions, more participation, and more equal contributions than individual commitments to a non-binding common goal à la Paris.
Keywords: C81; C93; F51; H87; Q54; 330; Climate Negotiations; Negotiation Design; Model United Nations; Uniform Carbon Price